PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS MELALUI PENERAPAN MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION (Studi Pada Siswa SMK Dr. Soetomo Surabaya) - Rusdiana, Eva; Sucipto, Sucipto (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2018)
This study aims to describe the application of the cooperative learning model of type group investigation (GI) in improving the ability of critical thinking mathematically. Research using qualitative approach to this type of classroom action research. The subject of research is the grade XI Accounting 1SMK Dr. Sutomo Surabaya totaled 41 students. Results of the study concluded that the application of the cooperative learning model of type group investigation (GI) proved to be able to improve the ability of critical thinking mathematically from very low to high category in two cycles. Based on the findings of the research are expected to mathematics teacher SMK Dr. Sutomo Surabaya make cooperative learning model type group investigation (GI) as an alternative to improve the ability of critical thinking mathematically students.